2022
DOI: 10.3390/ijerph19031897
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Symptoms in Chronic Cocaine Users: An Interpretative Model

Abstract: According to the latest estimates, there are around 24.6 million cocaine users worldwide, and it is estimated that around a quarter of the population worldwide has used cocaine at some point in their lifetime. It follows that such widespread consumption represents a major risk for public health. Long-term use of cocaine, in addition to being related to many cerebral and cardiovascular diseases, is increasingly associated with a higher incidence of psychomotor symptoms and neurodegenerative disorders. In recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Activation of the mesolimbic DA system is the neurobiological basis of cocaine addiction. Studies have shown that cocaine causes DA neurons in the VTA to release stored DA, increases the concentration of extracellular DA in DA neurons, and then leads to enhance DA release in the striatum and other nerve nuclei (41); the degree of psychomotor activation induced by cocaine is also related to the DA response (42). At the same time, cocaine blocks the re-uptake of DA by DAT (43).…”
Section: Mechanism Of Dopamine In Drug Addictionmentioning
confidence: 99%
“…Activation of the mesolimbic DA system is the neurobiological basis of cocaine addiction. Studies have shown that cocaine causes DA neurons in the VTA to release stored DA, increases the concentration of extracellular DA in DA neurons, and then leads to enhance DA release in the striatum and other nerve nuclei (41); the degree of psychomotor activation induced by cocaine is also related to the DA response (42). At the same time, cocaine blocks the re-uptake of DA by DAT (43).…”
Section: Mechanism Of Dopamine In Drug Addictionmentioning
confidence: 99%